2017
DOI: 10.3389/fmicb.2017.00462
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Enriched Microbial Consortium on Iron-Reducing Bioaugmentation in Sediments

Abstract: Microbial iron reduction is an important biogeochemical process and involved in various engineered processes, including the traditional clay dyeing processes. Bioaugmentation with iron reducing bacteria (IRB) is generally considered as an effective method to enhance the activity of iron reduction. However, limited information is available about the role of IRB on bioaugmentation. To reveal the roles of introduced IRB on bioaugmentation, an IRB consortium enriched with ferric citrate was inoculated into three F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Nearly complete reduction of SO 4 2− (15 mM) and Fe 3+ (5 mM) were noticed following 10–14 days of incubation, confirming their abilities for reduction of these terminal electron acceptors. The formation of black precipitates of iron sulfide in SRM and change in color of the IRM from yellow to light green or colorless with precipitation of Fe (Ferric citrate as redox indicator) (Pan et al, 2017) was also noted (Supplementary Figure S2). In order to confirm the presence of these SRB and IRB after 4 months of incubation where a decline in soluble iron concentration (Fe 2+ ) was observed due to precipitation with sulfide produced by sulfate reducing activity in the treatments, DGGE based microbial community analysis was performed with 5 months incubated microcosms (H_5M, C_5M, and C+L_5M).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Nearly complete reduction of SO 4 2− (15 mM) and Fe 3+ (5 mM) were noticed following 10–14 days of incubation, confirming their abilities for reduction of these terminal electron acceptors. The formation of black precipitates of iron sulfide in SRM and change in color of the IRM from yellow to light green or colorless with precipitation of Fe (Ferric citrate as redox indicator) (Pan et al, 2017) was also noted (Supplementary Figure S2). In order to confirm the presence of these SRB and IRB after 4 months of incubation where a decline in soluble iron concentration (Fe 2+ ) was observed due to precipitation with sulfide produced by sulfate reducing activity in the treatments, DGGE based microbial community analysis was performed with 5 months incubated microcosms (H_5M, C_5M, and C+L_5M).…”
Section: Resultsmentioning
confidence: 93%
“…Microbial taxa enriched during this study were reported to be of facultative- or strict-anaerobic nature, involved in anaerobic hydrolytic fermentation, cysteine utilization, acetate- and H 2 S-production and metal reduction (Petrie et al, 2003; Church et al, 2007; Finke and Jørgensen, 2008; Kosaka et al, 2008; Li et al, 2011; Bertel et al, 2012; AlAbbas et al, 2013; Hausmann et al, 2016; Peng et al, 2016; Pan et al, 2017). The major genera identified in this study such as Clostridium , Clostridium sensu stricto members, Lutispora , Sporobacter , Acetanaerobacterium , Caldicoprobacter , Gracilibacter , Oxobacter, Fonticella, Papillibacter , as well as unclassified members of Ruminococcaceae , Lachnospiraceae , and Christensenellaceae were all reported as anaerobic, fermentative, cellulose- and cysteine-metabolizing, acetogenic, and iron reducing members (Grech-Mora et al, 1996; Defnoun et al, 2000; Chen and Dong, 2004; Lee et al, 2006; Shiratori et al, 2008; Bouanane-Darenfed et al, 2011; Chen M. et al, 2013; Fraj et al, 2013; Peng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…); and Chloroflexi; Nitrospirae (such as Nitrospira); Bacteriodetes; Spirochaetes; Verrucomicrobia; Sphingobacteria (Lovley et al, 1998;Coates et al, 1999;Wilkins et al, 2007;Esther et al, 2015;Hori et al, 2015;Pan et al, 2017) while Fe(III)-reducing archaea include Euryarchaeota (e.g., Methanobacterium sp.) and Crenarchaeota (Pan et al, 2017). The concentration and type of organic matter available was found to control the communities of Fe(III)reducers (Lentini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among the corrosive microbes, iron reducing bacteria (IRB) and oxidizing bacteria (IOB) are two kinds of special microorganisms using iron as an electron acceptor and donor, respectively, (Byrne et al, 2015). IRB combine reduction of Fe(III) with oxidation of organic matter or H 2 for energy conservation, i.e., IRB readily use dissolved Fe(III) complexes or short-range-ordered minerals (e.g., ferrihydrite) and even magnetite as terminal electron acceptors (Pan et al, 2017; Fortney et al, 2018). IOB grow with Fe(II) or H 2 as the electron donor coupled to the reduction of oxygen in environments at acidic and circumneutral pH values (Weber et al, 2006; McBeth and Emerson, 2016).…”
Section: Introductionmentioning
confidence: 99%